Determining Factors of Contraception Method Selection Decisions For Fertile Age Couples in East Denpasar District - Hani Alifiyah; Ni Made Tisnawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Denpasar City has the highest number of babies born with a birth rate of 16,453 with a TFR of 1.85. In 2023, the number of fertile couples will be 13,459. Data analysis techniques usedin researchthis is binary logisticwithNagelkerke R Square value of 0.933 couples with a percentage of new acceptors of 48.56 percent. East Denpasar District is a district that has successfully implemented the family planning program which is an example for other areas. The purpose of this study was to analyze the husband's age, wife's age, income, husband's education, wife's education, and number of children on the decision to choose a contraceptive method for fertile couples in East Denpasar District. The results of this study indicate that 1) Husband's age, wife's age, income, husband's education, wife's education, and number of children have a simultaneous effect onprobabilitydecision on choosing a contraceptive method for fertile couples in East Denpasar District. 2) Partially, the husband's age, income, husband's education, and wife's education have a negative and significant effect onprobabilitydecision on choosing a contraceptive method for fertile couples in East Denpasar District. 3) The wife's age variable has a positive and significant effect onprobabilitydecision on choosing a contraceptive method for fertile couples in East Denpasar District. 4) The number of children does not affectprobabilitydecision on choosing contraceptive methods for fertile age couples in East Denpasar District.